Transformasi Digital dalam Hukum Administrasi Negara Analisis Implementasi CEISA 4.0 - Agus Pranoto (Jurnal Hukum Lex Generalis, 2026)
This article examines the implementation of CEISA 4.0 as a form of digital transformation in customs administration from the perspective of Indonesian State Administrative Law. The discussion focuses on the relationship between service digitalization, legality of administrative action, general principles of good governance, accountability, transparency, and protection of service users. The study applies a qualitative method with a normative juridical approach supported by document analysis of statutes, customs policies, and Indonesian scholarly articles published within the last five years. The findings show that CEISA 4.0 strengthens administrative efficiency, process standardization, audit trails, and integration of customs services. However, system effectiveness is not determined solely by the availability of the application. Network reliability, data interoperability, human resource capacity, continuity management during service disruption, and administrative complaint mechanisms remain decisive factors. From the perspective of State Administrative Law, CEISA 4.0 generally aligns with the principles of legality, legal certainty, utility, transparency, and proper public service, yet operational norms still need to be reinforced so that legal protection for service users does not depend on fragmented technical policies. This article recommends regulatory harmonization, stronger standard operating procedures, continuity governance, and broader digital literacy to support lawful, efficient, and accountable customs services.